Bacterial outer membrane vesicles and host cell death signaling. Issue 12 (December 2021) - Dhital, Subhash; Deo, Pankaj; Stuart, Isabella; Naderer, Thomas
Abstract : The programmed cell death pathways of pyroptosis and apoptosis protect mammals from infections. The activation of host cell death signaling depends on cell surface and cytosolic receptors that bind bacterial molecules or sense their activity. The formation of cytosolic protein complexes, such as the inflammasome and apoptosome, activates caspases, pore-forming proteins, and inflammatory cytokines. These pathways respond to bacteria and their released membrane vesicles. Outer membrane vesicles (OMVs) that emerge from the outer membrane of Gram-negative bacteria deliver a range of bacterial molecules, including lipids, proteins, polysaccharides and nucleic acids to host cells. Recent findings describe how OMV-associated molecules activate pyroptosis, apoptosis, and other inflammatory pathways. We discuss here how OMV-associated molecules are sensed by the immune system and how this contributes to infections and inflammatory diseases. Highlights: Pyroptosis and apoptosis control infection and inflammation. Bacterial outer membrane vesicles (OMVs) deliver a diverse set of molecules to host cells. Depending on the bacteria involved, OMVs induce pyroptosis or apoptosis. OMVs trigger inflammation and anti-inflammatory responses in animal models.